Clinical effectiveness of treatment of distal bite in children using modern orthodontic applainces - Mykhailovska, Лариса Олександрівна (Actual Dentistry, 2023)
Resume. The prevalence of bite pathology, which occupies one of the leading places among the dental morbidity of children and adolescents, is an urgent problem not only oforthodontics, but also of dentistry as a whole. Sagittal anomalies of the bite, in particular the distal one, cause significant damage not only to the child's health, but also to his social adaptation in society: they worsen the appearance, disrupt speech and the process of chewing food, are a risk factor for the development of caries, periodontal and temporomandibular joint diseases. The purpose of the study is to evaluate the effectiveness of the developed treatment scheme for children aged 5 to 8 years with a distal bite and impaired circular muscle function. Conclusions. The effectiveness of the developed treatment regimen for distal bite and oral circular muscle dysfunction in children aged 5 to 8 years based on data from dynamometry and electromyography of maxillofacial muscles has been proven.